COVID-19-associated angiitis: literature review and case report - D. I. Abdulganieva; N. G. Shamsutdinova; A. A. Gaibaryan (Современная ревматология, 2022)
The article systematizes information about various dermatological signs of a novel coronavirus infection – COVID-19. Special attention is paid to the phenomenon of COVID-19-associated angiitis. A clinical case of acroischemia associated with COVID-19 is described: on the 34th day after the onset of infection, a patient developed skin cyanosis of the distal parts of the fingers, which resolved spontaneously after a few days. The need for further research on the skin manifestations of COVID-19 and the development of an effective strategy for managing patients, as well as monitoring the condition of convalescents, is emphasized.